2019
DOI: 10.1097/spv.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Genital Hiatus to Normative Values After Apical Suspension Alone Versus With Level 3 Support Procedures

Abstract: Level 3 support procedures may be unnecessary to restore genital hiatus to normal at time of apical suspension procedures and should be reserved for select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…We hypothesized that preoperative GH rest would be associated with prolapse recurrence, as GH rest is strongly correlated with GH strain, 10 which has consistently been shown to be associated with prolapse recurrence. 6,8,9,14,15 However, we were unable to show an association between prolapse recurrence and preoperative GH rest or strain. One explanation for this difference may be related to the high colpoperineorrhaphy rate in the current study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We hypothesized that preoperative GH rest would be associated with prolapse recurrence, as GH rest is strongly correlated with GH strain, 10 which has consistently been shown to be associated with prolapse recurrence. 6,8,9,14,15 However, we were unable to show an association between prolapse recurrence and preoperative GH rest or strain. One explanation for this difference may be related to the high colpoperineorrhaphy rate in the current study.…”
Section: Discussioncontrasting
confidence: 60%
“…This study adds new information about the status of the GH by investigating GH rest and its relationship to prolapse recurrence. We hypothesized that preoperative GH rest would be associated with prolapse recurrence, as GH rest is strongly correlated with GH strain, 10 which has consistently been shown to be associated with prolapse recurrence 6,8,9,14,15 . However, we were unable to show an association between prolapse recurrence and preoperative GH rest or strain.…”
Section: Discussionmentioning
confidence: 88%
“…However, our study also demonstrated a reduction in GH when apical POP surgery is performed even without perineorrhaphy. Similarly, Carter-Brooks et al [ 7 ] found that perineorrhaphy may not be necessary for reduction of GH. Interestingly, the postoperative change in GH in the subgroup of patients undergoing sacrocolpopexy was smaller than that seen in those undergoing vaginal native tissue apical suspensions, and the change in GH was not significantly greater in those who had perineorrhaphy vs. no perineorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence indicating a relationship between GH and POP, no such evidence demonstrates that surgical correction of GH is effective in the prevention of POP recurrence. In fact, some recent retrospective evidence suggests that perineorrhaphy may not be necessary [ 7 , 8 ]. Moreover, there is a lack of understanding as to how the GH seen by the surgeon at the end of a POP surgery relates to the GH seen on physical exam at clinical follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Based on prior literature, the normative value of the genital hiatus (Gh) is approximately 3.4 cm, and postoperative Gh after posterior colporrhaphy and/or perineorrhaphy is approximately 2.8 cm, with standard deviation of approximately 1 cm [ 11 ]. A sample size of 24 would afford 80% power to detect a mean of paired differences of 0.6, with an estimated standard deviation of differences of 1.0, using an alpha level of 0.05 with a paired t -test.…”
Section: Methodsmentioning
confidence: 99%